HUBUNGAN PERILAKU SELF-MANAGEMENT DENGAN KUALITAS HIDUP PENDERITA HIPERTENSI DI PUSKESMAS MADURAN LAMONGAN - Soliha, Siti; Lestari, Trijati Puspita; Maghfiroh, Isni Lailatul (Coping: Community of Publishing in Nursing, 2023)
Increased blood pressure in people with hypertension will have an impact on decreasing quality of life. One of the efforts to prevent complications of hypertension is the application of self-management behavior. People with hypertension have good self-control if they are actively involved in caring behavior and making decisions that support their own health. The purpose of this study was to determine the relationship between self-management behavior and the quality of life of hypertensive patients at the Maduran Lamongan Health Center. This study used a cross-sectional approach to 88 hypertensive patientswho were recruited by consecutive sampling. Data were collected using a questionnaire on hypertension self-management behavior and the quality of life of hypertension sufferers and analyzed using the Spearman Rank test. The results showed that (89,8%) hypertensive patients had self-management behavior. The good one (87,5%) had a good quality of life. The results of the Spearman Rank test showed p = 0,000 (p < 0,05) and r = 0,914 which means that there is a significant relationship between self-management behavior and the quality of life of hypertensive patients with a very strong affinity. Hypertension sufferers who have good self-management behavior will have a high quality of life. Therefore, it is hoped that hypertension sufferers can improve self-management behavior by adopting a healthy lifestyle and routinely monitoring blood pressure at health facilities to achieve the desired quality of life want.